A Review on TiO2 Nanotube Film Photocatalysts Prepared by Liquid-Phase Deposition - Jinshu Wang; Qian Cai; Hongyi Li; Yuntao Cui; Hong Wang (International Journal of Photoenergy)
TiO2 nanotube film is a promising photocatalyst associated with its unique physical and chemical properties such as optic, electronic, high specific surface area. Liquid-phase decomposition provides a feasible way for the preparation of functional thin film. This paper reviews and analyzes the formation mechanism of TiO2 nanotube film by liquid phase deposition. The effect of preparation parameters, such as the kinds of electrolyte solution for the preparation of anodic alumina template, volume fraction of Al2O3 on the template, the concentration of the deposition solution, and heat treatment, on the formation of TiO2 nanotube film has been analyzed. The effects of doping of metallic and nonmetallic elements on the photocatalytic activity of TiO2 nanotube have been discussed.